Long-Term Effects of the 1923 Mass Refugee Inflow on Social Cohesion in Greece - Murard, Elie (World Bank, Washington, DC, 2022)
After the 1919–1922 Greco-Turkish conflict, 1.2 million Greek Orthodox were forcibly displaced from Turkey to Greece, increasing the host population by 20 percent within a few months. Refugees were pro-vided with farmland, new houses and schools, and were granted the Greek citizenship. This paper analyses the long-term social integration of refugees and the effect of their resettlement on social cohesion. Combining historical and modern population censuses and surveys, this paper finds that, by the 2000s, refugees display a high rate of intermarriage with Greek natives, report levels of trust in others and in institutions similar to natives, and exhibit higher political and civic participation. At the community level, places with a higher share of refugees in 1928 are more likely to have at least one sport association 80 years later. There is no impact on political fragmentation nor on crime. The historical refugees’ integration starkly contrasts with the social marginalization of recent Albanian immigrants who, unlike the former, neither spoke Greek nor had the same religion as locals upon arrival. These results suggest that early investments in inclusion policies can be effective at fostering refugees’ assimilation, at least when newcomers and locals have similar cultural profiles.